ANALISIS ALIH KODE DAN CAMPUR KODE DALAM FILM GAMPANG CUAN KARYA RAHABI MANDRA - Rani Safitri; Edi Rohaedi (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
The objective of this research is to describe the processes of code switching and code mixing, as well as the factors influencing them. This study employs a descriptive qualitative research method. The data source for this research is the movie Gampang Cuan by Rahabi Mandra, in video format. The data collection technique used in this research is listening and noting, which involves observing and recording utterances found in the movie Gampang Cuan by Rahabi Mandra. The instrument used for analysis is a data card. The research findings reveal 30 instances of internal code switching and 8 instances of external code switching. For code mixing, there are 50 instances in word form, 23 instances in phrase form, and 7 instances in clause form. The factors influencing code switching include the speaker factor 14 instances, the interlocutor factor 14 instances, the topic change factor 8 instances, and the arrival of a third person factor 2 instances. The factors influencing code mixing include the speaker factor 39 instances, the interlocutor factor 15 instances, the topic change factor 24 instances, and the change form to informal factor 2 instances.